2021
DOI: 10.1186/s12931-021-01766-0
|View full text |Cite
|
Sign up to set email alerts
|

Intralymphatic immunotherapy with tyrosine-adsorbed allergens: a double-blind, placebo-controlled trial

Abstract: Background Most previous studies used aluminum hydroxide-absorbed allergen extracts in evaluating the potential therapeutic roles of intralymphatic allergen-specific immunotherapy (ILAIT). In this study, we evaluated the therapeutic efficacy and safety of ILAIT with L-tyrosine-adsorbed allergen extracts of Dermatophagoides farinae, D. pteronyssinus, cat, dog, or mixtures thereof, in patients with allergic rhinitis induced by these allergens. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 32 publications
(78 reference statements)
1
30
0
Order By: Relevance
“…With the exception of studies by Witten et al ( 23 ) and Park et al ( 43 ), in which ILIT was associated with negative results, ILIT has been widely reported to decrease reactivity to allergens in allergy skin tests and nasal allergen provocation tests, alleviate allergic symptoms, and reduce rescue medication use. These therapeutic effects have been observed within 4 months after treatment initiation ( 17 18 19 20 22 24 25 44 45 46 47 48 49 ).…”
Section: Therapeutic Efficacy Of Aits With Alternative Routes Of Admi...mentioning
confidence: 98%
See 4 more Smart Citations
“…With the exception of studies by Witten et al ( 23 ) and Park et al ( 43 ), in which ILIT was associated with negative results, ILIT has been widely reported to decrease reactivity to allergens in allergy skin tests and nasal allergen provocation tests, alleviate allergic symptoms, and reduce rescue medication use. These therapeutic effects have been observed within 4 months after treatment initiation ( 17 18 19 20 22 24 25 44 45 46 47 48 49 ).…”
Section: Therapeutic Efficacy Of Aits With Alternative Routes Of Admi...mentioning
confidence: 98%
“…Notably, meta-analyses have shown that ILIT significantly reduces CSMSs ( Fig. 2A ) ( 23 26 43 45 47 48 50 51 ). Regarding the negative results reported by Witten et al ( 23 ), Kündig et al ( 52 ), who first introduced ILIT for allergic diseases, suggested that a 2-week interval between intralymphatic injections may be insufficient.…”
Section: Therapeutic Efficacy Of Aits With Alternative Routes Of Admi...mentioning
confidence: 99%
See 3 more Smart Citations